Peningkatan Kompetensi Tutor Blok Elektif dalam Pembuatan dan Penilaian Laporan Kasus - Titiek Djannatun; Riyani Wikaningrum; Rita Rita Murnikusumawatie; R. W. Susilawati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Elective block of the Faculty of Medicine YARSI University offers five topics. The evaluation results found a variation of tutor competence in writing and grading the case reports. The aims of this study is to improve the tutors’ competence in writing and grading Case Report.Method: Ten Case reports were selected and assessed by the study team. Thirty Tutor participated in the workshop. The tutor competence in the assessment case reports were analysed by pre test and post test compared with expert. Tutors’ performance was analyzed using the inter-rater reliability and students feedback using questioner.Results: This study found that 13 tutors gave lower absolute number of grade after the workshop, range from 1 to 14 points, and 3 tutors gave higher grade range from 3 to 6 points, and 5 tutors gave the same grade. The differences between the tutors’ and standard widened in 9 (42.9%) shortened in 9 (42.9%), and the same in 3 (14.3%). The workshops have a positive impact on achieving similar perception case report writing and grading. Conclusion: The case report grading must be done by tutors who have the same competence and perception of each grading item. The workshop gave the positive impact to the tutor as a rater. Case report grading with rubric to get a fair and valid must be assessed by more tutors.